Between Text and Discourse: Re-Theorizing Islamic Orthodoxy. (1st April 2018) - ,
Abstract : This article will examine the concept of orthodoxy as it appears in the work of Talal Asad and two of his interlocutors, namely Ovamir Anjum and Shahab Ahmed. In response to Ahmed's critique of Asad which attempts to dislocate orthodoxy as constitutive of Islam, this article employs the distinction Anjum draws between local and universal orthodoxy and theorizes it from a discourse-theoretical perspective. Hence, it will be argued that universal orthodoxy is central to Islamic discursive tradition because it is the limit which preserves Islam's singularity and allows it to exist as a unified universe of meaning. Furthermore, against Ahmed's contention that orthodoxy cannot account for Islamic philosophy 1 and Sufism as Islamic discourses because it is an inherently exclusionary concept, I will demonstrate that exclusionary limits are necessary for the formation of all discourses including Sufism and Islamic philosophy. Displacing orthodoxy effectively amounts to subverting the singularity of Islam and reproduces the pitfalls of anti-essentialist approaches.